Negosiasi Identitas Budaya melalui Praktik Bahasa Hibrida dalam Komunikasi Antar Santri di Pondok Pesantren Multikultural (Studi Etnografi Komunikasi) : Penelitian - Abdullah Bessam NH; Nikmah Suryandari (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
The cultural diversity found in multicultural Islamic boarding schools creates communication dynamics that encourage students to adapt their interactions. This study aims to analyze the process of cultural identity negotiation through hybrid language practices in communication among students at Al-Kaukabuddurri Islamic Boarding School, Bangkalan. The research employed a constructivist paradigm with a qualitative approach using the ethnography of communication method. The participants consisted of six students from Madurese, Javanese, and Sundanese ethnic backgrounds, along with two supporting informants, namely boarding school administrators and teachers, selected through purposive sampling. Data were collected through non-participant observation, in-depth interviews, documentation, and literature review. The data were analyzed using the interactive model of Miles, Huberman, and Saldana and validated through source triangulation. The findings reveal that cultural identity negotiation occurs through communication adaptation, characterized by language adjustment, learning other regional languages, and the use of Indonesian as a bridging language. This process gives rise to hybrid language practices that facilitate shared understanding, strengthen social relationships, and support intercultural communication. The study further demonstrates that hybrid language functions not only as a communication strategy but also as a symbol of students' collective identity without diminishing their original cultural identities. These findings contribute to intercultural communication studies by positioning hybrid language as an outcome of cultural identity negotiation within a multicultural Islamic boarding school community.